Administrative Employee Performance Management in Improving School Administrative Services at Mts Al Fathimiyah Karawang - Nurhaelah Nurhaelah; Abubakar Umar; Yadi Fahmi Arifudin (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
One way to improve the quality of human life is through education, especially Islamic education which includes moral, material and spiritual aspects. In an Islamic educational institution, of course, it has a school administrative order or what is commonly referred to as administration. Administration is a big part of the administrative process, administration is a mechanism that can help, expedite, and increase the activity and efficiency of the administrative process. The purpose of this study is to find out how the efforts of administrative staff improve administrative services through the management function. This study used a descriptive qualitative method by conducting observations, interviews and documentation. The results of the study show that planning and organizing the performance of administrative staff at MTs Al Fathimiyah Karawang has gone well, this is shown through the planning of work programs and the distribution of job descriptions according to the ability of each administrative staff; the implementation and supervision of the performance of administrative staff at MTs Al Fathimyah Karawang has been going quite well, this is indicated by the implementation of the work program and the supervision and evaluation carried out by the head of the madrasa.